Steven Ungar. Critical Mass: Social Documentary in France from the Silent Era to the New Wave. U of Minnesota P, 2018. - Mary McCullough (Studies in 20th & 21st Century Literature, 2019)
Review of Steven Ungar. Critical Mass: Social Documentary in France from the Silent Era to the New Wave. U of Minnesota P, 2018. Xxii + 300pp.
Keywords: Film; France; Documentary